(untitled) (ҚазҰУ хабаршысы. Экономика сериясы, 2017)
In the theory and practice of cost accounting for the environment (environmental costs) there are a number of controversial issues associated with their classification, identification of hidden costs and their distribution between types of products, etc. As practice shows, organizations can’t always mainstream media environmental costs to determine the share of individual products (works, services) in the emissions of the organization and other kinds of environmental pollution. As practice shows, the absence of specific accounting standard for the costs of environmental protection measures, does not preclude reporting in this area. In addition, the standards of any country refers to the possibility of submission of additional information together with the financial statements. The report on environmental activities it is advisable to make and present in those sectors in which the protection of the environment can be assessed as substantial. The formation of reliable, accurate and timely information about the costs of environmental protection measures enterprises need to take decisions about the introduction of synthetic accounts and subaccounts.